ANALISIS KADAR GLUKOSA DARAH SEBELUM DAN SESUDAH OPERASI BERDASARKAN LAMA OPERASI DI RSUP Dr. M. DJAMIL PADANG - Jefri Henky; Zayrina Suhada (Nusantara Hasana Journal, 2024)
Glucose functions as the human body main fuel which is responsible for producing energy. Risk factors are related to blood glucose levels: age, genetics, exercise habits, diet, stressors/trauma, smoking habits, obesity. The duration of surgery can affect blood glucose levels and cause the anesthesia to take longer, which can have an impact on blood glucose levels. The stress response to surgery is a change in the metabolic and hormonal systems, responses resulting in an increase in blood glucose levels or reactive hyperglycemia. To analyze of blood glucose levels pre and post operative based on duration of surgery at Dr. M. Djamil Hospital, Padang. This research using a cohort study design with T-test analysis. The sample in this study was selected using consecutive sampling techniques and the number of samples in this study 54 patients. The highest mean of blood glucose levels were found at the neurosurgery, which was 111.20+18.62 mg/dL in preoperative and 182.60+58.94 mg/dL in postoperative. The highest mean of blood glucose levels were found in the severe duration of surgery (>120 minutes), 94.69+16.90 mg/dL in preoperative and 122.19+42.37 mg/dL in postoperative with significant increase (p<0.05). The severe duration of surgery increased postoperative blood glucose levels.